Connectors for electrical and electronic equipment. Product requirements. Circular connectors. Detail specification for connectors with outer or inner push-pull locking mechanism, based on mating interfaces according to IEC 61076-2-101, IEC 61076-2-109, IEC 61076-2-111 and IEC 61076-2-113 Part 2-010, (31st August 2021) - British Standards Institution,
No abstract available